استخدام محاسبة التكاليف في أحتساب تكاليف المؤسسات التعليمية: دراسة تطبيقية في جامعة بغداد (Journal of Accounting and Financial Studies ( JAFS ), 2009)
The institutions of higher education and scientific research are the strategic institutions in the field of investing the human resources. Expenditure on such institutions is considered a long – term investment. Thus, the financial balancing in such institutions is not a traditional one.These institutions are not for profit organizations.Accordingly, they need to have accounting data that are calculated on an agreed upon cost basis due to the continuous growth in the expenditure on the services rendered by these institutions. These calls for the availability of tools that help rationalize the expenditure.Cost Accounting system is capable of providing the useful data for such purposes and guiding the work of these institutions as well as getting to the costs of services in order to compare them with the quality of the rendered services to achieve the aim of providing the best service with the least possible cost.